Religiosity and its effects on financial reporting quality of publicly listed companies from 3 ASEAN countries with COVID-19 as a moderator: A PLS-SEM model study - Laurena, Javier Francisco B. (Animo Repository, 2021)
This paper aims to determine if religiosity affects the financial reporting quality of firms during COVID-19. Prior studies have shown that religiosity has an influence on financial reporting quality. The group would like to research if this remains true during COVID-19. The financial statements of publicly listed non-financial companies coming from Malaysia, Philippines and Singapore were chosen as samples for this study. COVID-19, as the moderating variable, will be measured through cases per one million citizens per country, while financial reporting quality will be measured using a time series analysis of discretionary accruals using the modified Jones model. Religiosity, the independent variable in this study, will be measured using the average of three dimensions of religion adapted from the World Values Survey questionnaire. The three control variables for this paper are Firm Size, Leverage and Return on Assets. The data gathered was analyzed using Partial Least Square - Structural Equation Model (PLS-SEM) using WarpPLS software. PLS-SEM is typically analyzed and interpreted sequentially in two stages to ensure that measures of constructs are reliable and valid before determining the nature of the relationships of the variables. Results showed that religiosity has a significant impact on financial reporting quality. On the other hand, COVID-19 did not pose a moderating effect between the relationship of religiosity and financial reporting quality.